Kinetics and Mechanism of Oxidation of Malonic Acid with Bi(V) in HClO4-HF Mixture - MOHAN PRASAD, CHANDRA; MOHAN MISHRA, PREM; SHEKAR JHA, CHANDRA (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of malonic acid with Bi(V) has been investigated in HClO4 (1.0 M) and HF (1.50 M) mixture. The rate followed first order kinetics each in Bi(V) and malonic acid. The reaction rate is independent of [H+]. Addition of HF and (F+) ion has not effect on the reaction rate. The reaction rates decreased with the increase in ionic strength. The mode of electron transfer from the substrate to Bi(V) has been indicated via bridged outer sphere mechanism.